1997
DOI: 10.1111/j.1744-7348.1997.tb05788.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on viability of imbibed weed seeds

Abstract: Imbibed seed of 10 common arable weeds were placed in trays in initially moist soil and, after imbibing for 2 h, heated in ovenshncubators set to 31°C 42"C, 56°C 75°C or 100°C for 0.5, 1, 2, 4, 8 or 16 days or at 102"C, 155"C, 204°C or 262°C for 0.5, 1, 2, 5, 7.5 or 10 min. After heating, seeds were incubated for 28 days at 10/20"C or 20130°C on a 12 h darwlight regime, depending on species, and germination recorded. At the lower temperatures, germination of all species was prevented by temperatures of 75°C or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 10 publications
7
29
0
2
Order By: Relevance
“…Viability of seeds with a soft seed coat (dandelion, stinkweed, wild oat) was reduced (P < 0.05) after exposure to compost, compared to that of control seeds and was not affected by level of liquid manure applied. For these three weed species, reduction of viability showed a simple linear relationship with compost temperature ( Figure 6) in accord with Thompson et al (1997) who established 48°C as the critical temperature for elimination of viability of wild oat. In contrast, viability of buckwheat which has a hard seed coat was improved (P < 0.05) in LO and MED treatments as compared to non-composted seeds (Control).…”
Section: Weed Seed Viabilitysupporting
confidence: 85%
See 1 more Smart Citation
“…Viability of seeds with a soft seed coat (dandelion, stinkweed, wild oat) was reduced (P < 0.05) after exposure to compost, compared to that of control seeds and was not affected by level of liquid manure applied. For these three weed species, reduction of viability showed a simple linear relationship with compost temperature ( Figure 6) in accord with Thompson et al (1997) who established 48°C as the critical temperature for elimination of viability of wild oat. In contrast, viability of buckwheat which has a hard seed coat was improved (P < 0.05) in LO and MED treatments as compared to non-composted seeds (Control).…”
Section: Weed Seed Viabilitysupporting
confidence: 85%
“…The weed seeds were chosen as they varied in seed coat characteristics and resistance to inactivation during composting. The temperatures and conditions required for inactivation of these seeds during composting have been established (Thompson et al 1997;Eghball and Lesoing 2000;Larney and Blackshaw 2003) and are analogous to those required to inactivate many pathogens (Hess et al 2004;Cekmecelioglu et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Dry storage at 35°C for 10 wk reduced seed dormancy, such that subsequent incubation at temperatures between 10 and 25°C increased germination to 100%. Thompson et al (1997) observed that exposure of initially dormant, imbibed seeds to temperatures greater than 31°C reduced germination after dormancy had broken. Germination decreased from 67 to 58% at 31°C, as time of exposure increased from 0.5 to 16 d. Germination of seeds exposed to temperatures of 42°C for 16 d fell to 47%.…”
Section: Reproductionmentioning
confidence: 99%
“…Though autoclave treatment is a common means of seed inactivation in modern laboratories, few references exist for this method of seed destruction. However, published literature supports heat as an effective means of inactivating seed (Dahlquist et al, 2007;Thompson et al, 1997). High moisture conditions and allowing seeds to imbibe water may contribute to the efficacy of heat-based seed destruction.…”
Section: Malendia Maccreementioning
confidence: 99%